Sodium dodecyl sulfate-ethoxylated polyethylenimine adsorption at the air-water interface: how the nature of ethoxylation affects the pattern of adsorption. - Batchelor, SN; Tucker, I; Petkov, J; Penfold, J; Thomas, R (American Chemical Society, 2014)
The strong interaction between ionic surfactants and polyelectrolytes of opposite charge results in enhanced surface adsorption at the air-water interface down to low surfactant concentrations and in some cases in the formation of ordered surface structures. A notable example which exhibits such properties is the mixture of polyethylenimine, PEI, and sodium dodecyl sulfate, SDS. However, the electrostatic interaction, around charge neutralization, between the surfactant and polymer often results in precipitation or coacervation. This can be mitigated for PEI-surfactant mixtures by ethoxylation of the PEI, but this can also result in a weaker surface interaction and a significant reduction in the adsorption. It is shown here that by localizing the ethoxylation of the PEI into discrete regions of the polymer precipitation upon the addition of SDS is suppressed, the strong surface interaction and enhanced adsorption of the polymer-surfactant mixture is retained. The adsorption of SDS in the presence of ethoxylated PEI is greatly enhanced at low SDS concentrations compared to the adsorption for pure SDS. The adsorption is equally pronounced at pH 7 and 10 and is largely independent of the degree of ethoxylation. Surface ordering, more than monolayer adsorption, is observed over a relatively narrow range of SDS concentrations and is most pronounced at pH 10 and for the polymers with the lower degree of ethoxylation. The results show that ethoxylated PEI's reported here provide a suitable route to enhanced surfactant adsorption while retaining favorable solution properties in which precipitation effects are minimized.